Association of Cerebral Blood Flow With Longitudinal Changes in Cerebral Microstructural Integrity in the Coronary Artery Risk Development in Young Adults (CARDIA) Study - Bouhrara, Mustapha; Triebswetter, Curtis; Kiely, Matthew; Bilgel, Murat; Dolui, Sudipto; Erus, Guray; Meirelles, Osorio; Bryan, Nick R; Detre, John A; Launer, Lenore J (JAMA Network Open, 2022)
IMPORTANCE: Decreased cerebral tissue integrity and cerebral blood flow (CBF) are features of neurodegenerative diseases. Brain tissue maintenance is an energy-demanding process, making it particularly sensitive to hypoperfusion. However, little is known about the association between blood flow and brain microstructural integrity, including in normative aging. OBJECTIVE: To assess associations between CBF and changes in cerebral tissue integrity in white matter and gray matter brain regions. DESIGN, SETTING, AND PARTICIPANTS: In this longitudinal cohort study, magnetic resonance imaging was performed on 732 healthy adults from the Coronary Artery Risk Development in Young Adults (CARDIA) study, a prospective longitudinal study (baseline age of 18-30 years) that examined participants up to 8 times during 30 years (1985-1986 to 2015-2016). Cerebral blood flow was measured at baseline (year 25 of the CARDIA study), and changes in diffusion tensor indices of fractional anisotropy (FA) and mean diffusivity (MD), measures of microstructural tissue integrity, were measured at both baseline and after approximately 5 years of follow-up (year 30). Analyses were conducted from November 5, 2020, to January 29, 2022. MAIN OUTCOMES AND MEASURES: Automated algorithms and linear mixed-effects statistical models were used to evaluate the associations between CBF at baseline and changes in FA or MD. RESULTS: After exclusion of participants with missing or low-quality data, 654 at baseline (342 women; mean [SD] age, 50.3 [3.5] years) and 433 at follow-up (230 women; mean [SD] age, 55.1 [3.5] years) were scanned for CBF or FA and MD imaging. In the baseline cohort, 247 participants were Black (37.8%) and 394 were White (60.2%); in the follow-up cohort, 156 were Black (36.0%) and 277 were White (64.0%). Cross-sectionally, FA and MD were associated with CBF in most regions evaluated, with lower CBF values associated with lower FA or higher MD values, including the frontal white matter lobes (for CBF and MD: mean [SE] β = −1.4 [0.5] × 10−6; for CBF and FA: mean [SE] β = 2.9 [1.0] × 10−4) and the parietal white matter lobes (for CBF and MD: mean [SE] β = −2.4 [0.6] × 10−6; for CBF and FA: mean [SE] β = 4.4 [1.1] × 10−4). Lower CBF values at baseline were also significantly associated with steeper regional decreases in FA or increases in MD in most brain regions investigated, including the frontal (for CBF and MD: mean [SE] β = −1.1 [0.6] × 10−6; for CBF and FA: mean [SE] β = 2.9 [1.0] × 10−4) and parietal lobes (for CBF and MD: mean [SE] β = −1.5 [0.7] × 10−6; for CBF and FA: mean [SE] β = 4.4 [1.1] × 10−4). CONCLUSIONS AND RELEVANCE: Results of this longitudinal cohort study of the association between CBF and diffusion tensor imaging metrics suggest that blood flow may be significantly associated with brain tissue microstructure. This work may lay the foundation for investigations to clarify the nature of early brain damage in neurodegeneration. Such studies may lead to new neuroimaging biomarkers of brain microstructure and function for disease progression.